Influence Good Governance on the Quality of Financial Statements with SIMDA as Variables Moderating Government in Pati Regency - Wijayanti Wijayanti; Warno Warno; Ari Kristin P (Journal of Islamic Economics and Social Science (JIESS), 2020)
This study aims to determine how much influence the good governance has on the quality of financial statements and to find out how much SIMDA in moderating the effect of good governance on the quality of financial statements. Quality financial statements will narrow down actions to commit corruption or other fraud. Every year the financial statements will be audited by the Supreme Audit Board and the issuance of opinions on the financial statements that have been audited. The method used in this study is quantitative with primary data from questionnaires. The sample used is probability sampling. The results of the study obtained that good governance has a positive and significant effect on the quality of financial statements. This is evidenced from the significance of 0,000 <0, 05 and tcount> ttable (5.475> 1.679). Whereas SIMDA can "strengthen" the effect of good governance on the quality of financial statements. These results are proven from the interaction test graph which illustrates if SIMDA becomes a moderating variable the effect of good governance on the quality of financial statements.